Management of directors and quality of educational service in a school parish of the Callao region - Cruz Cárdenas, César Augusto (2021)
The present work was oriented to investigate about the existing nexus between the management of the directors of a parochial school in the Callao region and the quality of service provided to the educational community. A quantitative, cross-sectional, correlational study was carried out. For data collection, two questionnaires were prepared (one per variable), with Likert-type responses. The sample was made up of 150 students, 62 teachers, 23 administrators and 90 parents. The contrast was made by means of Pearson's correlation coefficient, which yielded a value of 0.897, which corresponded to a high positive correlation. The values for the managerial leadership dimensions were 0.863; for the strategic planning dimension it was 0.825; while for the management evaluation dimension 0.857 was obtained and for the institutional coexistence dimension 0.804. It was concluded that a direct and strong correlative correlation did occur between the management of the governing body and the quality of the educational service. More detailed aspects are suggested for future research in this regard.